Relationship between service quality and customer loyalty: mediating effect of customer satisfaction and customer trust in Thailand’s audit firms - Pringviriya, Nuchsara (2015)
Customer loyalty is a competitive tool for companies. The growth and survival of companies depend on how loyal their customers are, and the audit firm is no exception. Customer loyalty has played an important role in achieving competitive advantages. Customer loyalty can increase a company’s income, reduce costs and lead to future revenue. The major drivers of customer loyalty are service quality, customer satisfaction, and customer trust. Therefore, this study explores the relationship among service quality, customer satisfaction, customer trust, and customer loyalty and determines the mediating effect of customer satisfaction and customer trust on the relationship between service quality and customer loyalty in Thailand’s audit firms. The SERVQUAL model is an important instrument used to measure service quality in this study. The respondents of the study are public companies listed on the Stock Exchange of Thailand. The auditors are under Thailand’s laws and regulations and are approved by the office of the Stock Exchange of Thailand to audit the Securities and Exchange Commission registrants. A total of 507 questionnaires were distributed, and only 296 questionnaires were received. Seven hypotheses were developed and tested with multiple regression and hierarchical regression analysis. The results indicate that the SERVQUAL model is a good measurement of service quality in an audit firm. Firstly, service quality has a strong positive relationship with customer satisfaction, customer trust, and customer loyalty. Secondly, customer satisfaction has a positive relationship with customer loyalty. Thirdly, customer trust has a positive relationship with customer loyalty. Finally, customer satisfaction and customer trust partially mediate the relationship between service quality and customer loyalty. Plausible reasons for the results are discussed within the context of the study. Both practical and theoretical contributions, as well as recommendations for future research made.